2015
DOI: 10.11648/j.ijber.20150406.13
|View full text |Cite
|
Sign up to set email alerts
|

Customer’s Attitude Towards Mobile Advertising in Bangladesh

Abstract: In the age of information communication technology (ICT) uses of mobile phone or cell phone is increasing and business environment of Bangladesh is becoming more competitive day by day. Most of the companies strive to maximize their sales volume and use advertisements to promote their products and services. The main objective of the study is to examine the customer's attitude towards mobile advertising in Bangladesh. Through which marketers can scan the real scenario about the customer's attitude towards the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 23 publications
1
8
0
2
Order By: Relevance
“…Incentives: Advertisers communicate advertising messages via mobile phones and sometimes give incentives in exchange (Tsang et al, 2004), which influence customer attitudes towards mobile advertising (Hossain et al, 2017). This point is further corroborated by Dharmadasa and Alahakoon (2014) and Huq et al (2015), who found that incentive-based mobile advertisements trigger positive customer attitudes towards mobile advertising.…”
Section: Widely Used Constructssupporting
confidence: 59%
“…Incentives: Advertisers communicate advertising messages via mobile phones and sometimes give incentives in exchange (Tsang et al, 2004), which influence customer attitudes towards mobile advertising (Hossain et al, 2017). This point is further corroborated by Dharmadasa and Alahakoon (2014) and Huq et al (2015), who found that incentive-based mobile advertisements trigger positive customer attitudes towards mobile advertising.…”
Section: Widely Used Constructssupporting
confidence: 59%
“…Additionally, it is time to apply the effectiveness of green advertising while emphasizing the environmental benefits of the green product, promoting a sustainable lifestyle, improving the green image of the brand, and reducing the characteristic imperfections of green products [169,170]. Most consumers respond positively to green ads (e.g., print and television ads) [171,172] that predict customer purchase intention. Dangelico and Vocalelli remarked that producers and supply need to provide complete, accurate, and easy-to-understand information about a lifelong environment [3].…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Pola pertumbuhan eksponensial yang mirip dengan penyebaran virus, viral marketing message disarankan sebagai strategi pemasaran hemat biaya yang mendorong business performance (sales) dalam waktu singkat dan memfasilitasi hubungan (engagement) antara perusahaan dan pembeli potensial (Dobele et al, 2007). Adopsi konsep mobile advertising (melalui viral marketing message) yang memiliki konsistensi pesan yang baik akan berdampak lebih besar pada business performance (sales) perusahaan dan juga memiliki frekuensi jangkauan yang baik serta memengaruhi eksposur yang berbeda ke target audiens dibandingkan beriklan melalui tradisional (seperti Iklan TV atau cetak) (Majedul Huq, 2015). Viral marketing adalah strategi yang menggunakan komunikasi peer-to-peer untuk meningkatkan kesadaran dan adopsi produk atau layanan di seluruh jaringan pembeli yang luas (Xiong & Hu, 2010).…”
Section: Business Performanceunclassified
“…Selain itu, penelitian dari Majedul Huq (2015) yang meneliti tentang consumers' attitude towards mobile advertising di Bangladesh juga mendukung hasil penelitian ini. Perbedaan penelitian Majedul Huq (2015) dengan penelitian ini adalah pada jumlah dimensi yang digunakan untuk viral marketing message ada lima yaitu perceived entertainment, credibility, reward, technological familiarity, dan message frequency, sedangkan pada penelitian ini hanya ada empat dimensi yaitu informativeness, entertainment, irritation, dan source credibility.…”
Section: Viral Marketing Message Terhadap Consumers' Attitude Towards Viral Marketingunclassified